ANALISIS TITIK KESETIMBANGAN DAN KESTABILAN PENYEBARAN PENYAKIT MALARIA DI DISTRIK MANOKWARI BARAT BERDASARKAN MODEL EPIDEMIK SIR - Fandy Fandy; Andi Fajeriani Wyrasti; Tri Widjajanti (FMIPA Universitas Papua, 2009)
Stability and equilibrium of malaria’s epidemics in Manokwari Barat district based on SIR epidemic model will be discussed in this paper. The SIR epidemic model can be applied to make a model of endemic diseases like malaria. Based on this research, there are 2 types of the equilibrium of malaria’s epidemics in Manokwari Barat District, endemic and non endemic point.